Fascia Iliaca Block for Postoperative Pain Control After Hip Arthroscopy: A Systematic Review of Randomized Controlled Trials. Issue 14 (December 2021) - Smith, John-Rudolph H.; Kraeutler, Matthew J.; Keeling, Laura E.; Scillia, Anthony J.; McCarty, Eric C.; Mei-Dan, Omer
Background: Various analgesic modalities have been used to improve postoperative pain in patients undergoing hip arthroscopy. Purpose: To systematically review the literature to compare the efficacy of the fascia iliaca block (FIB) with that of other analgesic modalities after hip arthroscopy in terms of postoperative pain scores and analgesic consumption. Study Design: Systematic review. Methods: A systematic review was performed by searching PubMed, the Cochrane Library, and Embase up to April 2020 to identify randomized controlled trials that compared postoperative pain and analgesic consumption in patients after hip arthroscopy with FIB versus other pain control modalities. The search phrase used was "hip arthroscopy fascia iliaca randomized." Patients were evaluated based on postoperative pain scores and total postoperative analgesic consumption. Results: Five studies (3 level 1, 2 level 2) were identified that met inclusion criteria, including 157 patients undergoing hip arthroscopy with FIB (mean age, 38.3 years; 44.6% men) and 159 patients among the following comparison groups: lumbar plexus block (LPB), intra-articular ropivacaine (IAR), local anesthetic infiltration (LAI), saline placebo, and a no-block control group (overall mean age, 36.2 years; 36.5% men). No significant differences in pain scores were reported in the postanesthesia care unit (PACU) between the FIB and LPB (3.4 vs 2.9; P = .054), IAR (7.7 vs 7.9; P = .72), control group (no FIB: 4.1 vs 3.8; P = .76); or saline placebo (difference, –0.2 [95% CI, –1.1 to 0.7]). One study reported significantly higher pain scores at 1 hour postoperation in the FIB group compared with the LAI group (5.5 vs 3.4; P = .02). Another study reported significantly greater total analgesic consumption (in morphine equivalent dosing) in the PACU among the FIB group compared with the LPB group (20.8 vs 17.0; P = .02). No significant differences were observed in total PACU analgesic consumption between FIB and other analgesic modalities. Conclusion: In patients undergoing hip arthroscopy, the FIB does not appear to demonstrate superiority to other forms of analgesics in the immediate postoperative period. Therefore, it is not recommended as a routine form of pain control for these procedures.